Commonwealth Caribbean public law - Fiadjoe, Albert (Cavendish Pub. LondonGB, 1999)
Deals with Commonwealth Caribbean public law in five sections titled: the ambit of public law; legitimate expectations of the citizenry; select issues in constitutional law, select issues in administrative law, and the reform process. Examines topics such as: separation of powers, conventions of the constitution, safeguards og judicial independence; and, the ombudsman.